Characterization of Non-Highly Compressed Iron Powders in Ring Form for Application in the Field of Electrical Machines - Torabi Shahbaz, Mohammad; Wöckinger, Daniel; Marth, Edmund; Bramerdorfer, Gerd (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
In this study, non-highly compressed iron powders in a ring-shaped sample container are characterized. This approach involves the dimensioning of a non-magnetic ring-shaped container to measure the magnetic properties of ferromagnetic powders with different bulk densities. Therefore, an optimization of the container’s dimensions is presented. Finally, the precise data acquisition systems for determining the material’s B-H characteristics and loss curves in relevant operating points are discussed and first measuring results for several distinct material densities are presented.